Kolyvagin Derivatives of Modular Points on Elliptic Curves - Hatton, Richard (2020)
Let E/Q and A/Q be elliptic curves. We can construct modular points derived from A via the modular parametrisation of E. With certain assumptions we can show that these points are of infinite order and are not divisible by a given prime p. We can also show that the group generated by these points is isomorphic to a representation of the projective general linear group.